Evaluation of the kinematic behavior of a series of stations Geocentric System for the Americas processed with Precise Point Positioning online. - Moya Zamora, Jorge (2014)
By calculation mode in Precise Point Positioning (PPP) online, processed more than two years of daily observations of 14 continuously operating stations belonging to Geocentric System for the Americas (SIRGAS), which are strategically located on the Caribbean Plate. Under the assumption that in a PPP development can achieve accuracy greater than that provided by commercial software calculation, we used the results of this processing option to make a comparison of the data with respect to offered weekly by SIRGAS which are of high quality and accuracy and analyze their level of agreement. This comparison allowed for a description of the kinematic motion of the area concerned, based on the fact that precisely the differences in the time series, as in SIRGAS, are due to the movement themselves. In online processing tool available was used by the Canadian Spatial Reference System (CSRS) on its website, with which processed more than 7000 files daily. After purification of the results could be obtained in an average difference of the velocity values in the XYZ coordinates of the stations -0.8 mm/a, +2.2 mm/ay +1.9 mm/a with data regarding SIRGAS.